1994
DOI: 10.1016/0928-8244(94)00007-7
|View full text |Cite
|
Sign up to set email alerts
|

Heat shock response in Actinobacillus actinomycetemcomitans

Abstract: The heat shock response in Actinobacillus actinomycetemcomitans, a capnophilic Gram-negative bacterial species that is implicated in the development of certain forms of periodontitis, was characterized. Different strains of A. actinomycetemcomitans were grown at 37, 42 and 48 degrees C in the presence of 35S-methionine. The bacterial cells were lysed, run on SDS-PAGE and subsequently blotted on nitrocellulose paper. After autoradiography of the blots, several protein bands from the cultures at 42 degrees C sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
15
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 14 publications
1
15
1
Order By: Relevance
“…There have been studies which reported (i) detection of common stress proteins in oral microorganisms (7)(8)(9), (ii) cloning of these stress proteins (10,24,43), (iii) demonstration of potent induction of bone resorption (16,30), or (iv) purification of specific heat shock proteins from various Hsp families (4,10,14,20,23,39,40,44). There have been several studies that reported an association between periodontal disease and titers of antibody to Hsp65 and Hsp90 in serum (17,22,24,31).…”
mentioning
confidence: 99%
“…There have been studies which reported (i) detection of common stress proteins in oral microorganisms (7)(8)(9), (ii) cloning of these stress proteins (10,24,43), (iii) demonstration of potent induction of bone resorption (16,30), or (iv) purification of specific heat shock proteins from various Hsp families (4,10,14,20,23,39,40,44). There have been several studies that reported an association between periodontal disease and titers of antibody to Hsp65 and Hsp90 in serum (17,22,24,31).…”
mentioning
confidence: 99%
“…Like other pathogenic microorganisms, an important homeostatic mechanism that both P. gingivalis and A. actinomycetemcomitans mount when exposed to elevated temperature is a heat shock response ( (Lu and McBride, 1994;Vayssier et al, 1994;Lokensgard et al, 1994). The heat shock response is a highly conserved response to elevated temperature found in both prokaryotes and eukaryotes.…”
Section: Temperaturementioning
confidence: 99%
“…The heat shock response in A. actinomycetemcomitans was originally studied by Koga et al (9) and by Løkensgard et al (10). Cloning and molecular characterization of the genes encoding GroEL and DnaK of A. actinomycetemcomitans have also been reported (9,11,12).…”
Section: Introductionmentioning
confidence: 99%